Preliminary Trials with High Yielding Varieties of Leucaena leucocephala - Lonani, D. N. (Indian Forester, 1979)
Leucaena leucocephala is a high quality legume of the tropics and several fast growing strains give high yield of forage and wood. Several strains of fast growing leucaena were obtained in 1976-77 and tried in different locations in U.P., both in plains and hills. The experience gained from the trials is described Varieties K8 and Fiji have shown good growth in saline-alkaline soils and varieties K8, K62 and K-29 in other areas in the plains.